Análise da influência da pressão de injeção, contrapressão ambiente e tipo de combustível nos parâmetros da atomização de um injetor de injeção direta de combustível high-pressure swirl - Carlos Alberto Gomes Junior (2017)
The physical phenomena that occur in the spray formed by the fuel injectors used in internal combustion engines have been widely studied by researchers worldwide. The interest in studying these phenomena arises from the need to reduce fuel consumption and pollutant emissions, to increase the engine combustion efficiency and analyze the behavior of different of fuel being placed on the market. In the present work, experiments were carried out to analyze the influence of injection pressure, ambient backpressure and test fluid type on the atomization parameters (macroscopic and microscopic) of the high-pressure swirl injectors spray. As test fluids were used: water, anhydrous ethanol (EA), ethanol fuel (E100), gasoline (E0), gasoline (E22), Exxsol D40 and Exxsol D60. An experimental device consisting of two nitrogen cylinders, an injection system control (Motec-M84 along with a peak and hold injection driver), a fuel tank as pressure vessel and a high-speed camera (CCD) and LEDs for back-light illumination. The macroscopic characteristics (cone angle and penetration) of the spray were determined using footage at 8000 frames per second, And a shadowgraph technique was applied with the aid of MatLab for the treatment of the images and the microscopic ones were measured with the PDA (Phase Doppler Anemometry), to determine mean droplet velocity, droplet diameter and characteristic mean diameters, with emphasis on the Mean Diameter and Sauter Mean Diameter (SMD) of the Exxsol D40 spray with the injection pressures of 80, 100 and 120 bar. The results showed a similar behavior between the fuels and the Exxsol D40, for the macroscopic and for microscopic characteristics show that the quality of the atomization improves with the increase of the injection pressure, that is, smaller droplet diameters and higher droplet velocities.